Carbon Dioxide as a Microbial Toxicity Enhancer of Some Antibacterial Agents: A New Potential Water Purification Tool. (22nd April 2012) - Martirosyan, Varsik; Hovnanyan, Karlen; Ayrapetyan, Sinerik
Abstract : The aim of current paper was to investigate the possibility of increasing the toxicity of calcium hypochlorite (Ca(ClO)2 ) and hydrogen peroxide (H2 O2 ) on Escherichia coli K-12 by preliminary enrichment of culture media by carbon dioxide (CO2 ). For this purpose, the microbes sensitivity to H2 O2 or/and Ca(ClO)2 at normal and CO2 -enriched medium was studied by spectrophotometric, radioisotopic, and electronmicroscopic methods. Ten-minute preincubation in CO2 -enriched medium enhanced the toxic effect of both H2 O2 or/and Ca(ClO)2 on bacteria as a result of induced growth inhibition, compared to no-CO2 enriched group. Additionally, changes in cell morphology and proliferation were observed. It was demonstrated that the preliminary incubation of microbes in CO2 -enriched culture media in nonsupercritical concentration elevate the toxic effect of H2 O2 or/and Ca(ClO)2 on microbes. This can serve as a novel, effective, inexpensive, and environmentally friendly approach for water purification from bacteria, further improving the protection of the environment and human health.